ISLAMIC SELF-AFFIRMATION PARADIGM: A RESPONSE TO THE SOCIAL CHALLENGES OF MODERN MEDIA - Pramesti, Nadila Putri; Romadhoni, Pratiwi Uly; Sofian, Muhamad; Febriyanti, Nur Ilmi Putri; Yazid, Afthon (Research Institute and Community Engagement of UIN MADURA, 2025)
In the midst of modernity and globalization, Muslim individuals face various social challenges that can trigger identity crises and self-confidence issues. Self-affirmation according to the Islamic paradigm can be a solution to overcome these challenges. This research aims to analyze the Islamic paradigm of self-affirmation as a response to social challenges. The research method used is qualitative with literature studies, sourced from the Quran, Hadith, and the works of Islamic scholars. The results of the research show that the Islamic paradigm of self-affirmation emphasizes the strengthening of Islamic beliefs and values within individuals. Self-affirmation is carried out by strengthening faith and piety to Allah SWT, recognizing one's potential as a noble creature of Allah, emulating the Prophet Muhammad SAW and his companions, living life according to Islamic law, and being optimistic and never giving up. In conclusion, the Islamic paradigm of self-affirmation not only enhances self-confidence but also encourages individuals to become better and more beneficial members of society.